2018
DOI: 10.1371/journal.pone.0202368
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of total phenolic content from Terminalia chebula Retz. fruits using response surface methodology and evaluation of their antioxidant activities

Abstract: Ultrasonic-assisted extraction (UAE), using aqueous ethanol as the solvent, was firstly applied to extract phenolic compounds from Terminalia chebula Retz. fruits (T. chebula fruits). In this study, ethanol concentration (%), ultrasonic intensity (W/cm2), particle diameter (mm), extraction temperature (°C), ultrasonic time (min), liquid-solid ratio (mL/g) and extraction cycle were investigated by single-factor experiment and then optimized using a Box-Behnken design. The optimized result for UAE was 68% ethano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 38 publications
2
28
0
Order By: Relevance
“…Its bioactive components extracted from the leaves, bark and fruit of the plant include flavonoids, polyphenols, terpenes, anthocyanins, glycosides, gallic acid, chebulagic acid, punicalagin, chebulanin, corilagin, neochebulinic acid, ellagic acid, chebulinic acid, alkaloids and many more [ 232 , 237 , 284 ]. It is also known to be used as a cure for irregular fevers, urinary diseases, diabetes, skin diseases, heart diseases, constipation, ulcers, vomiting, colic pain, hemorrhoids, digestive diseases, and others [ 232 , 235 , 237 ]. However, T. chebula has many pharmacological activities such as antiviral, antioxidant, antibacterial, antifungal, anti-protozoal, anti-carcinogenic, anti-mutagenic, radio-protective, chemo-preventive, hepato-protective, cardio-protective, cyto-protective, anti-diabetic, reno-protective, anti-inflammatory, anti-arthritic, adaptogenic, anti-anaphylactic, hypolipidemic, hypocholesterolemic, anti-caries, wound healing, anti-allergic, immunomodulatory, anti-ulcer, anti-spasmodic and gastrointestinal motility properties [ 232 , 233 , 235 , 236 , 237 ].…”
Section: Other Medicinal Plants In Use Against Various Viral Infecmentioning
confidence: 99%
See 1 more Smart Citation
“…Its bioactive components extracted from the leaves, bark and fruit of the plant include flavonoids, polyphenols, terpenes, anthocyanins, glycosides, gallic acid, chebulagic acid, punicalagin, chebulanin, corilagin, neochebulinic acid, ellagic acid, chebulinic acid, alkaloids and many more [ 232 , 237 , 284 ]. It is also known to be used as a cure for irregular fevers, urinary diseases, diabetes, skin diseases, heart diseases, constipation, ulcers, vomiting, colic pain, hemorrhoids, digestive diseases, and others [ 232 , 235 , 237 ]. However, T. chebula has many pharmacological activities such as antiviral, antioxidant, antibacterial, antifungal, anti-protozoal, anti-carcinogenic, anti-mutagenic, radio-protective, chemo-preventive, hepato-protective, cardio-protective, cyto-protective, anti-diabetic, reno-protective, anti-inflammatory, anti-arthritic, adaptogenic, anti-anaphylactic, hypolipidemic, hypocholesterolemic, anti-caries, wound healing, anti-allergic, immunomodulatory, anti-ulcer, anti-spasmodic and gastrointestinal motility properties [ 232 , 233 , 235 , 236 , 237 ].…”
Section: Other Medicinal Plants In Use Against Various Viral Infecmentioning
confidence: 99%
“…It is also known to be used as a cure for irregular fevers, urinary diseases, diabetes, skin diseases, heart diseases, constipation, ulcers, vomiting, colic pain, hemorrhoids, digestive diseases, and others [ 232 , 235 , 237 ]. However, T. chebula has many pharmacological activities such as antiviral, antioxidant, antibacterial, antifungal, anti-protozoal, anti-carcinogenic, anti-mutagenic, radio-protective, chemo-preventive, hepato-protective, cardio-protective, cyto-protective, anti-diabetic, reno-protective, anti-inflammatory, anti-arthritic, adaptogenic, anti-anaphylactic, hypolipidemic, hypocholesterolemic, anti-caries, wound healing, anti-allergic, immunomodulatory, anti-ulcer, anti-spasmodic and gastrointestinal motility properties [ 232 , 233 , 235 , 236 , 237 ]. Lin et al, 2013 conducted an in vitro study and found that chebulagic acid and punicalagin from the fruit of T. chebula have the potential to inhibit the activity of different viruses, such as human cytomegalovirus, HCV, dengue virus, measles virus, and respiratory syncytial virus [ 234 ].…”
Section: Other Medicinal Plants In Use Against Various Viral Infecmentioning
confidence: 99%
“…In another study, Sheng et al (2018) used ethanol as an extraction solvent and examined the effect of different concentration of ethanol (0%, 20%, 40%, 60%, 80%, and 100%) on total phenolic content from Terminalia chebula Retz. fruits using response surface methodology [19]. They noted that 60% ethanol gives higher extraction yield than other tested concentrations of ethanol.…”
Section: Discussionmentioning
confidence: 99%
“…Sheng et al evaluated antioxidant activities of phenolic compounds extracted from Terminalia chebula Retz. fruits by different extraction methods like UAE and LLE [26]. The results showed that, the antioxidant activities of phenolic compounds extracted by UAE under optimized condition were stronger than LLE method.…”
Section: Ultrasound-assisted Extraction (Uae)mentioning
confidence: 96%